The Effect of Economic Literacy and Lifestyle on Consumptive Behavior of PT VIRTUS facility service South Jakarta employees - Sutisna, Ahmad; Purnamasari, Sulfi (International Journal of Economics Education Research (IJEER), 2022)
This study aims to determine (1) the effect of economic literacy on the consumptive behavior of PT Virtus facility service employees (2) the effect of lifestyle on the consumptive behavior of PT Virtus facility service employees (3) the simultaneous effect of economic literacy and lifestyle on the consumptive behavior of PT Virtus facility service employees. This research is a type of quantitative research. The variables in this study consisted of the dependent variable consumptive behavior (Y), and the independent variable was economic literacy (X1) lifestyle (X2). The population in this study were all employees of PT Virtus facility service which amounted to 60 people with sampling using the Slovin formula. Respondents in this study amounted to 54 employees of PT Virtus facility service. Sampling technique with the type of Simple Random Sampling. Data collection techniques using a questionnaire. The data analysis technique used in this research is descriptive and inferential statistical analysis technique with tests of normality, linearity, multicollinearity, heteroscedasticity, simple linear regression, and multiple linear regression. The results of this analysis indicate that: (1) There is a positive and significant effect of economic literacy on the consumptive behavior of PT Virtus facility service employees with a t-value of 18.422 > 1.677. (2) There is a positive and significant effect of lifestyle on the consumptive behavior of PT Virtus facility service employees with a t value of 14.818 > 1.677. (3) There is a positive and significant effect of economic literacy and lifestyle simultaneously on the consumptive behavior of PT Virtus facility service employees. In the output R Square (0.892) the results of the consumptive behavior variable (Y) are influenced by economic literacy variables (X1) and lifestyle (X2) by 89.2% and the remaining 10.8% is influenced by other variables outside the study. And the simultaneous significant test (statistical test F) where sig 0.000 <0.05.